RELAXOTERAPIA PRIN CARTE PENTRU COPIII ȘI TINERII CU CERINȚE EDUCAȚIONALE SPECIALE - TIMUȘ, director, Filiala „Maramureș”, Angela (BIBLIOPOLIS, 2020)
The „Maramures” Branch represents an element, a unit of the cultural and educational sphere designed to ensure the continuity of the processus of recovering and development of people with special educational needs. The range of special needs is huge and is destined to the category: “people with disabilities”. The relaxation therapy represents one of the most eficient treatment for this category of users which assure emotional balance. In this connection the library is seen as an oasis of silence and relaxion. Relaxing through book of persons with disabilities includes information, socialization and communication, the ultimate goal being to obtain general satisfaction.